FAUN TAIL - Khan, Shahbaz Ali; Zadran, Khalid Khan (Journal of Ayub Medical College Abbottabad, 2016)
A 13 years old presented in neurosurgery out-patient with dorsal backache and difficulty in walking. Clinical examination revealed localized hypertrichosis in the mid-dorsal region without hyper-reflexia in both lower limbs with no motor defect or sphincter disturbances. MRI and CT scan revealed underlying diastometamyelia and a bony spur causing cord tethering. Patient was operated upon and the cord was detethered. Patient recovered well after the surgery with improvement of presenting symptoms. Hypertrichosis is a dermatological condition characterized by excessive growth of hair on non-androgen dependent areas of body. Primary hypertrichosis can either be localized or generalized. The primary localized variety may occur as hypertrichosis cubiti that involves the elbows, anterior cervical hypertrichosis, posterior cervical hypertrichosis or a faun tail deformity.1 The word faun refers to an Italian deity in human form with horns, pointed ears with goat's legs and tail.2 In certain racial groups such as African American, Asian and Hispanic, hypertrichosis in the lumbosacral region may be a normal entity. A faun tail is an abnormal congenital lock of course, triangular-shaped, terminal hair situated on the lumbosacral area of various lengths.3 It is an important cutaneous marker of underlying spinal abnormalities like spinal dysraphism. Other cutaneous markers of such spinal abnormalities include dimples, dermal sinuses, subcutaneous lipomas, port wine stain, hemangiomas, aplasia cutis, telengiectasia, capillary malformation acrochordons, hemangiomas, aplasia cutis, etc. Yet, among some races like African American, Asian and Hispanic, hypertrichosis in the lumbosacral region may be a normal entity.2 It is important for the clinicians to be pick up the cutaneous markers of spinal abnormalities at early stages so that the neurosurgical consultation can be made before the overt manifestation of neurological symptoms are picked. Since the outcome of surgical intervention may not be that fruitful once the neurology starts to deteriorate.